Evaluation of the Anti-Inflammatory Effect of Ethanol Extract of Porang Tuber (Amorphophallus muelleri Blume) on White Rats (Rattus norvegicus) - Annisa Amaliah; Safriani Rahman; Aulia Wati (Universitas Muslim Indonesia, 2026)
Inflammation is a protective response to tissue injury aimed at neutralizing or eliminating invasive organisms triggered by physical trauma. One of the plants known for its anti-inflammatory properties is the porang tuber, which contains flavonoids. This study aimed to determine the anti-inflammatory effect and effective dosage of ethanol extract of porang tuber (Amorphophallus muelleriÂ Blume) in male rats (Rattus norvegicus). An experimental design was employed, utilizing 20 white rats divided into five treatment groups: a negative control (1% NaCMC), a positive control (sodium diclofenac), and porang tuber ethanol extract at doses of 100 mg/kgBW, 200 mg/kgBW, and 400 mg/kgBW. Test preparations were administered one hour before the induction of 1% carrageenan (0.1 mL, intraplantar). Paw edema volume was measured plethysmographically every 60 minutes for 6 hours. Statistical analysis, performed via one-way ANOVA followed by a Bonferroni post-hoc test, revealed no significant difference between the positive control group and the porang tuber ethanol extract groups. In conclusion, the porang tuber ethanol extract exhibits anti-inflammatory effects, with a dose of 400 mg/kgBW identified as the most effective.